Influence of education with video on Posyandu cadres knowledge about contraceptive implant - Suharniati, Rohma; Yunita, Laurensia; Mariana, Frani; Kabuhung, Elvine Ivana (Health Sciences International Journal, 2026)
Background: The low uptake of Long-Term Contraceptive Methods, particularly implants, in Indonesia is often linked to limited community knowledge and prevalent misconceptions. Posyandu cadres, as frontline health promoters, play a pivotal role in providing counseling; however, their own knowledge levels are frequently inadequate, hindering effective family planning promotion. Objective: Determine the influence of education using video media on the knowledge of Posyandu cadres about contraceptive implants in the working area of the Jejangkit Community Health Center. Method:  A quantitative pre-experimental study with a one-group pre-test-post-test design was conducted. A total of 30 cadres were selected via simple random sampling. Data were collected using a validated questionnaire administered before and after a single-session intervention featuring an educational video on contraceptive implants. The non-parametric Wilcoxon Signed-Rank Test was used for data analysis due to the non-normal distribution of the knowledge scores. Result: The study revealed a significant improvement in cadres' knowledge post-intervention. Prior to the video education, only 23.3% of cadres had good knowledge. Following the intervention, this proportion rose dramatically to 83.3%, with the remaining 16.7% achieving a sufficient level. No cadres remained in the poor knowledge category. Statistical analysis confirmed this improvement was highly significant (p < 0.001). Conclusion: Video-based education is a highly effective intervention for significantly enhancing the knowledge of Posyandu cadres regarding contraceptive implants. Integrating this media into regular training programs is recommended to empower cadres with accurate information, thereby improving community counseling and supporting national efforts to increase long-term contraceptive methods uptake.